Conrad and impressionism - Peters, John G. (Cambridge University Press, 2001)
In this book, John Peters investigates the impact of Impressionism on Conrad and links this to his literary techniques as well as his philosophical and political views. Impressionism, Peters argues, enabled Conrad to encompass both surface and depth not only in visually perceived phenomena but also in his narratives and objects of consciousness, be they physical objects, human subjects, events or ideas. Conrad and Impressionism investigates the sources and implications of Conrad's impressionism in order to argue for a consistent link between his literary technique, philosophical presuppositions and socio-political views.